2022
DOI: 10.1177/17411432221127655
|View full text |Cite
|
Sign up to set email alerts
|

Principal–teacher gender (dis)similarity as a moderator in the relationship between paternalistic leadership and organisational citizenship behaviour in the Arab minority in Israel

Abstract: Relying on the similarity attraction paradigm and self-categorisation theories, the current study examines how principal–teacher gender (dis)similarity affects the emergence of paternalistic leadership and the influences of such leadership on teachers’ organisational citizenship behaviour in the Arab minority in Israel. Data were collected from a sample of 180 randomly selected teachers and their principals from elementary schools in the Arab education system in Israel (180 dyads). MANCOVA, ANCOVA, hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…However, teachers' appraisal of PDM was higher compared to PL- authoritarian . These findings coincide with recent studies showing that PL- benevolent and PL- moral leadership is effective and positively related to employee feelings in a collectivist society with high-power distance (Abbas and Ilaiyan, 2021; Nassir and Benoliel, 2022). Perhaps, because as indicated in the research of Dimmock and Tan (2013), school principals displaying PL- benevolent, and PL- moral demonstrate integrity and conscientiousness and serve as selfless models while devoting full attention to their teachers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, teachers' appraisal of PDM was higher compared to PL- authoritarian . These findings coincide with recent studies showing that PL- benevolent and PL- moral leadership is effective and positively related to employee feelings in a collectivist society with high-power distance (Abbas and Ilaiyan, 2021; Nassir and Benoliel, 2022). Perhaps, because as indicated in the research of Dimmock and Tan (2013), school principals displaying PL- benevolent, and PL- moral demonstrate integrity and conscientiousness and serve as selfless models while devoting full attention to their teachers.…”
Section: Discussionsupporting
confidence: 92%
“…Following ILT, because individuals have their own ideas about the nature of leaders and leadership, they develop idiosyncratic theories of leadership. Therefore, teachers' appraisals of PDM and PL are likely to be influenced by cultural differences (Taras et al, 2010;Nassir and Benoliel, 2022). For example, in a collective society with a high-power distance, the subordinates are not ready to be involved in decision-making and prefer superiors that decide and give instructions which they would follow passively.…”
Section: Teacher Stress In the Israeli Arab Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, teachers in Arab society perceive the job of the principal as essentially a man’s job with an autocratic and nonparticipative style of management and male domination (Massry-Herzallah & Arar, 2019). Nevertheless, in recent decades, a process of “Israelisation” has taken place through which the Arab minority or certain groups or individuals within this society experience modernization, marked by rising living and educational standards and a rise in the status of women (Nassir & Benoliel, 2022).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…However, studies show that the Arab minority in Israel has undergone a broad, gradual and fundamental process of change from a traditional patriarchal and collectivist local identity (based on the village and Hamula—the extended family in the widest sense, or clan) to a more individualistic identity (Nassir & Benoliel, 2023; Saadeh & Suifan, 2020). Accordingly, the present study proposes to focus on the Israeli Arab educational system because research has shown that perceptions of leadership practices and the resulted teachers’ behaviors that are legitimate in one culture may not be in another (Hallinger, 2018; Nassir & Benoliel, 2022, 2023).…”
mentioning
confidence: 99%